Le Système Comptable et Financier Algérien un état des lieux et perspectives - CHACHOUA, ABDELKRIM (Finance and Business Economies Review, 2018)
Several historical factors have slowed down the organization of the accounting profession in Algeria. Moreover, the mode of national economic regulation through centralized planning has contributed to this delay. Nevertheless, a transition towards a more open market economy is currently engaged. Companies and private banks are allowed, and the financial market has started its activities. These important changes require a real development of the profession to meet the new needs of investors and to ensure the quality of accounting services. Algerian companies have been using the accounting and financial system of companies since 2010; however, we are left with standards that are beginning to be more and more out of date, compared to their international counterparts